Continuities and discontinuities in Italian politics (1943-1948) - Adinolfi, Goffredo (2009)
The objective of this article is to analyze continuities in the Italian political elite during the period of transition from authoritarianism to democracy (1943-1948). It outlines both the biographies of the ministerial elites and their political and professional careers, seeking to assess to what extent fascism/anti-fascism was a significant variable in the consolidation of the new political elite and, above all, whether this produced a new class or whether the former liberal elite merely regained its former position.